2012 IEEE International Conference on Industrial Technology 2012
DOI: 10.1109/icit.2012.6209934
|View full text |Cite
|
Sign up to set email alerts
|

Design, modeling and simulation of a miniaturized gas ionization sensor: Optimization of the structure and operation

Abstract: Gas ionization sensor (GIS), made of two parallel plates, works on measuring the breakdown voltage of gases that is unique for each gas. The gas breakdown inside the gas chamber occurs due to the ionization of gas molecules by accelerated electron impacts. The acceleration of electrons is very depended on the effective electric field they experience. It is shown that metallic or semiconductor nanowires grown between the two plates improve the sensitivity of the device and breakdown voltages of the gases are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…However, the observed time response was dominated by the filling and evacuating speed of our gas chamber rather than the true response time of the sensor. In fact, the theoretical simulation suggested that the ionisation process had the breakdown time scale of several nano seconds [48].…”
Section: Gis Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the observed time response was dominated by the filling and evacuating speed of our gas chamber rather than the true response time of the sensor. In fact, the theoretical simulation suggested that the ionisation process had the breakdown time scale of several nano seconds [48].…”
Section: Gis Performancesmentioning
confidence: 99%
“…(2) gives higher discharge current density, J. E tip is the effective electrical field on the tip of the NRs, given by [48]: (3) where V is the voltage applied between electrodes and the d is the separation between the electrodes. The strength of E tip is, however, also significantly affected by the aspect ratio of the NRs determined by the ratio of their length to the radius.…”
Section: Gis Performancesmentioning
confidence: 99%
“…Electron impact ionization (EII) and field ionization (FI) processes were, respectively, proposed for nanomaterial configured as a cathode (Huang et al, 2009;Chivu and Kahrizi, 2013;Mahmood et al, 2013) and an anode (Longwitz et al, 2001;Huang et al, 2009). If the nanorod was biased as a cathode, electrons would be extracted form cathode and in turn be accelerated and impact with gas molecular.…”
Section: Resultsmentioning
confidence: 99%
“…If the nanorod was biased as a cathode, electrons would be extracted form cathode and in turn be accelerated and impact with gas molecular. Then the gas molecular would be ionized by electron bombardment (Longwitz et al, 2001;Huang et al, 2009;Chivu and Kahrizi, 2013;Mahmood et al, 2013). If the nanorod was biased as an anode, gases would be ionized near the surface of nanotips by strong field extraction of the most loosely bound electrons from gas molecules (Longwitz et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…As applying this voltage is not practical, to scale down the breakdown voltage of the gases, 1D nanostructures could be applied as one of the electrodes. Enhanced local electric field (E loc ) is created at the tip of the nanostructures due to non-uniform distribution of charged carriers [27,28]. Field enhancement factor (β) characterizes the level of influence of the 1D nanostructures onto the electrostatic field distribution and can be defined as the field gain coefficient (β = E loc /E app ) [27].…”
Section: Introductionmentioning
confidence: 99%